Pengaruh Diskon Terhadap Pembelian Impulsif Pengguna Shopee pada Mahasiswa Universitas Buana Perjuangan Karawang - Herdianti Zaeni, Putri Anastasya; Isyanto, Puji (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to analyze the effect of discounts on impulse purchases among Shopee users among students at Buana Perjuangan University, Karawang. The phenomenon of impulse buying is becoming increasingly common with the increasing use of e-commerce platforms, where discounts are often used as a marketing strategy to attract consumers. The research method used is quantitative with data collection techniques through questionnaires distributed to 200 students who actively use the Shopee application. The results of data analysis show that discounts have a significant influence on impulse buying behavior. College students tend to make more unplanned purchases when they find attractive discount offers. These findings indicate that discounts are an important factor in encouraging impulse purchases, which Shopee can exploit to increase sales. In addition, this research provides insight for e-commerce business players regarding the importance of discount strategies in attracting the student market segment.